The Mormon Tabernacle Choir : a biography - Hicks, Michael, 1956- (Music in American life., 2015)
The epic story of how an all-volunteer group founded by persecuted religious outcasts grew into a multimedia powerhouse synonymous with the mainstream and with Mormonism itself. Drawing on decades of work observing and researching the Mormon Tabernacle Choir, Michael Hicks examines the personalities, decisions, and controversies that shaped 'America's choir'.